EDUchallenge - Brala-Mudrovčić, Jasminka (knjige, 2022)
The articles collected in this volume bring the rich experiences of teachers/professors and their coping with the challenges they have faced in different fields of teaching. A number of articles highlight the content value of author videos, their practical usefulness in the classroom and the advantages of using such videos. Others deal with developing soft skills and bringing mindfulness and holistic experience into our daily lives.
Keywords: informacijsko-komunikacijska tehnologija; izobraževalna tehnologija; Izobraževanje; jezikovni pouk; književnost; komuniciranje; matematika; naravoslovje; osebnostni razvoj; Posvetovanja; pouk; šport; trajnostni razvoj; učenje; videoposnetki; vrednotenje znanja; zborniki